2017
DOI: 10.3233/nre-172249
|View full text |Cite
|
Sign up to set email alerts
|

Newly developed Learning and Verbal Memory Test (TAMV-I): Normative data for Spanish-speaking pediatric population

Abstract: Abstract. OBJECTIVE:To generate normative data for the Learning and Verbal Memory Test (TAMV-I) in Spanish-speaking pediatric populations. METHOD:The sample consisted of 4,373 healthy children from nine countries in Latin America (Chile, Cuba, Ecuador, Guatemala, Honduras, Mexico, Paraguay, Peru, and Puerto Rico) and Spain. Each participant was administered the TAMV-I as part of a larger neuropsychological battery. Free recall, memory delay and recognition scores were normed using multiple linear regressions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…The PPVT-III is used to assess the receptive vocabulary in individuals aged 2 to 90 years ( Dunn et al, 2010 ). Although the use of this tool in the case of indigenous population has been questioned due to the cultural biases inherent in the stimuli ( Leigh and Gong, 2008 ; Haitana, 2010 ), the PPVT version used in this study has been shown to have adequate psychometric properties (interclass coefficient 0.95, p < 0.001; Rivera and Arango-Lasprilla, 2017 ) and there is specific normative data for the Guatemalan pediatric population ( Rivera et al, 2017 ). The tool has 192 items in total, each one consisting of a sheet with 4 illustrations that show different images related to a concept.…”
Section: Methodsmentioning
confidence: 97%
“…The PPVT-III is used to assess the receptive vocabulary in individuals aged 2 to 90 years ( Dunn et al, 2010 ). Although the use of this tool in the case of indigenous population has been questioned due to the cultural biases inherent in the stimuli ( Leigh and Gong, 2008 ; Haitana, 2010 ), the PPVT version used in this study has been shown to have adequate psychometric properties (interclass coefficient 0.95, p < 0.001; Rivera and Arango-Lasprilla, 2017 ) and there is specific normative data for the Guatemalan pediatric population ( Rivera et al, 2017 ). The tool has 192 items in total, each one consisting of a sheet with 4 illustrations that show different images related to a concept.…”
Section: Methodsmentioning
confidence: 97%
“…For psychosocial assessment the following tests were used: Children Depression Inventory [35] (CDI), Revised Children's Manifest Anxiety Scale [36] (CMAS-R), Pediatric Quality of Life Inventory [37] (PedsQL) Parent-Report, and Adaptive Behavior Assessment System, Second Edition [38] (ABAS-II). All of these tests had normative data available for Spanish-speaking children and adolescents [39][40][41][42][43][44][45][46][47][48].…”
Section: Neuropsychological Evaluationmentioning
confidence: 99%
“…Normative data exists for use of the TAMV-I among Spanish-speaking pediatric samples from 10 countries and the commonwealth of Puerto Rico (i.e. Chile, Colombia, Cuba, Ecuador, Guatemala, Honduras, Mexico, Paraguay, Peru, Puerto Rico, and Spain;Rivera et al, 2017b;Rivera et al, 2017c).…”
Section: Introductionmentioning
confidence: 99%
“…ROCF scores) andRivera et al (2017b; TAMV-I scores) for Colombian sample, and byArango-Lasprilla et al (2017a; ROCF scores) andRivera et al (2017c; TAMV-I scores) for the other countries(Chile, Cuba, Ecuador, Guatemala, Honduras, Mexico, Paraguay, Peru, Puerto Rico and Spain).These adjusted z-scores for each raw score were calculated using the information provided in each final regression model in a three-step procedure: 1. The expected test score ( � ) is computed based on the fixed effect parameter estimated of the established final regression model in Eq.…”
mentioning
confidence: 99%